Microfinancing and Entrepreneurship Growth among Women in Ogun State, Nigeria - Oluwakemi Adeoti, G.; Tunji Siyanbola, T.; Folajimi Adegbie, F.; Olubukola Adekola, D. (Asian Journal of Managerial Science, 2021)
Entrepreneurship has continually been a tenacious tool in responding to global poverty. The last few decades recorded tremedous activities of women entrepreneurs. Funding is a critical challenge to present and prospective women entrepreneurs. Microfinancing contitutes a principal source of easy access to funds. Microfinancing comprises financial and non-financial services which could possibly be a driving force to women entreprenuship and empowerment. However, the presence of microfinancing is though visible but there is lack of necessary investigation revealing the impact of microfinancing on entrepreneurial activities among women. Also, repayment problems pose threats of continuity to both microcredit institutions and entrepreneurs. A number of repayment strategies are in existence but there is lack of necessary investigation showing the influence of these repayment strategies on entrepreneurship growth among women. The focus of this study was to evaluate how Microfinancing has influenced entrepreneurship growth among women. This study adopted survey research design and convenience sampling technique. The study concluded that microfinancing has a significant impact on entreprenuship growth among women in Ogun State, Nigeria. Moreover, the developed model would serve as a useful inspiring construct for researchers.